A revision of the parasitoid wasp genus Dolichogenidea Viereck (Hymenoptera, Braconidae) in the Neotropical region, with the description of 102 new species - Jose L. Fernandez-Triana; Caroline Boudreault; James B. Whitfield; Amelie Höcherl; M. Alex Smith; Winnifred Hallwachs; Daniel H. Janzen (ZooKeys)
The parasitoid wasp genus Dolichogenidea is currently the second most speciose within the subfamily Microgastrinae (Hymenoptera: Braconidae), with 366 world species known so far, but with hundreds awaiting to be described. Here, the fauna of the Neotropical region is revised, with an emphasis in the Area de Conservación Guanacaste (ACG), Costa Rica. In addition to 23 species previously recorded from the Neotropics, 102 additional species are described as new, increasing the regional and world richness to 125 and 468 species, respectively. All species are diagnosed and described by using a combination of basic morphology (dichotomous key and brief diagnostic descriptions) and, when available DNA COI barcodes, biology (host data and wasp cocoon strategy), and distribution data. Neither morphology, biology, nor molecular data alone were sufficient to unambiguously separate all taxa, as all approaches were found to have limitations, but the combination of all three approaches provided stronger support to species delimitation. Morphology allowed the inclusion of all known species, therefore building a foundation upon which to improve as more molecular and biological data become available and new species are discovered; however, it was not sufficient (or it was very difficult to use) to separate at least 15% of all species keyed out in the dichotomous key. DNA barcoding was better able to separate species, and it is likely to become the most efficient way to identify species in the near future; however, DNA failed to identify 8.3% of the species with molecular data available, in addition to one third of the described species currently lacking molecular data. Biological data is currently the most incomplete, with only 42% of the species having associated host information, with a strong data availability bias towards ACG specimens. A total of 11 Lepidoptera families are here recorded to be parasitized by Neotropical Dolichogenidea, mainly Depressariidae (34% of all host data available), Gelechiidae (17%), Crambidae (14%), Tortricidae (10%), Thyrididae (8%) and Pyralidae (7%). Most of the wasps seem to be monophagous or at most oligophagous, as 56% are known to only parasitize a single host species, whereas 23% parasitize two host species and 10% parasitize three hosts; in almost all cases, the hosts species belong to one genus (or related genera) in the same Lepidoptera family. Most species of Dolichogenidea are found between 400–1,500 m, but a few have been found at higher elevations, including a few examples higher than 3,000 m (Costa Rica) and 4,000–4,100 m in the Andes (South America). The following nomenclatural acts are proposed: 1) the genus Exoryza is synonymized under Dolichogenidea, syn. nov.; 2) a total of 16 species are transferred to Dolichogenidea as comb. nov., one species formerly in the genus Apanteles: Dolichogenidea croceicornis (Muesebeck, 1958) and all 15 species formerly placed within Exoryza (six of them from the Neotropics): Dolichogenidea asotae (Watanabe, 1932), Dolichogenidea belippicola (Liu & You, 1988), Dolichogenidea hylas (Wilkinson, 1932), Dolichogenidea mariabustosae (Fernandez-Triana, 2016), Dolichogenidea megagaster (de Saeger, 1944), Dolichogenidea minnesota (Mason, 1981), Dolichogenidea monocavus (Valerio & Whitfield, 2004), Dolichogenidea oryzae Walker, 1994, Dolichogenidea reticarina (Song & Chen, 2003), Dolichogenidea richardashleyi (Fernandez-Triana, 2016), Dolichogenidea ritaashleyae (Fernandez-Triana, 2016), Dolichogenidea rosamatarritae (Fernandez-Triana, 2016), Dolichogenidea safranum (Rousse & Gupta, 2013), Dolichogenidea schoenobii (Wilkinson, 1932) and Dolichogenidea yeimycedenoae (Fernandez-Triana, 2016); 3) Dolichogenidea yeimycedenoae (Fernandez-Triana, 2016) becomes a senior secondary homonym of Dolichogenidea yeimycedenoae Fernandez-Triana & Boudreault, 2019; therefore, Dolichogenidea cedenoae Fernandez-Triana & Boudreault, 2025 is a replacement name for Dolichogenidea yeimycedenoae Fernandez-Triana & Boudreault, 2019; 4) the following 102 species, all authored by Fernandez-Triana & Boudreault, are described as sp. nov.: D. aceituno, D. alanflemingi, D. alejandromarini, D. alerce, D. alexamasisae, D. alexandrei, D. alixhamiltonae, D. amazonas, D. anacamposae, D. andreamezae, D. angelsolisi, D. anikenpalolae, D. anniapicadoae, D. annlisterudae, D. annychaverae, D. antioquia, D. antjevirkusae, D. arenal, D. bernardoespinozai, D. beryllacosteae, D. bradzlotnicki, D. caldas, D. carlosalvaradoi, D. carlosviquezi, D. chichicastenango, D. christinaagapakisae, D. claudiadoblesae, D. dole, D. encruzilhada, D. ericpalolai, D. ericsimoni, D. escobarae, D. felipechavarriai, D. frankjoycei, D. fredhicksi, D. helenedumasae, D. heredia, D. ingredolsonae, D. isabelleae, D. isidrochaconi, D. jaimelewisi, D. jasonkelleyi, D. jennyphillipsae, D. jessiehillae, D. johnrobinsoni, D. jorgecarvajali, D. jorgecortesi, D. josephfridmani, D. joshdarfleri, D. juanmatai, D. junhyongkimi, D. kasiiya, D. katiemccluskeyae, D. kenzabaddouae, D. lacochaparamo, D. leahdennisae, D. limoncocha, D. luishamiltoni, D. luzmariaromeroae, D. machupichu, D. mehdirheljari, D. moniqueae, D. moniquegilbertae, D. ninamasisae, D. nothofagus, D. oiketicus, D. palenque, D. papallacta, D. paulfryi, D. pedroleoni, D. puschendorfi, D. putumayo, D. puyo, D. rexhamiltoni, D. robertofernandezi, D. robinsherwoodae, D. robmacewani, D. robpringlei, D. rociocordobae, D. rodrigogamezi, D. ronaldzunigai, D. rubymacpearsae, D. rudyamadori, D. sallydaleyae, D. sarahoconnorae, D. scottmilleri, D. shelleymcsweeneyae, D. sigifredomarini, D. stephmae, D. stevestroudi, D. susanabramsae, D. teremariae, D. tiboshartae, D. timrichi, D. tomdaleyi, D. tristanpalolai, D. tucuman, D. verobrondexae, D. virgendelparamo, D. weaversway, D. yungas, D. yvesbraeti.